Ketogenic diet treatment in adults with glycogenosis type IIIa (Morbus Cori). (December 2019) - Fischer, Tobias; Njoroge, Helen; Och, Ulrike; Klawon, Ira; Marquardt, Thorsten
Summary: Background: Glycogen storage disease type IIIa (GSDIIIa) is a defect of the debranching enzyme (amylo-1, 6-glucosidase) in glycogenolysis and has an effect on the muscles and the liver. The guidelines for diagnosis and management of GSDIIIa primarily recommend a nutritional therapy to avoid hypoglycaemia. For adolescents and adults, the recommendation is a diet high in protein (25 E%) and moderate or low in carbohydrates (<50 E%) while avoiding simple sugars and fasting. There are some indications that a ketogenic diet, such as the modified Atkins diet (MAD), could present a good approach to nutritional therapy for GSDIIIa. Methods: This report is a retrospective evaluation of the nutritional and clinical data of two adult patients with GSDIIIa. The effect of a diet according to the guidelines and a ketogenic diet (MAD) were compared in both cases. Patient compliance during the nutrition therapy is also described. Results: The MAD led to a reduction of CK and a stabilization of blood glucose as well as to an unwanted weight loss. The progression of the disease was decelerated, but existing complaints could not be improved. Compliance to the MAD decreased over time and re-training was necessary. Conclusions: The MAD presents a good option for nutritional therapy for glycogenosis with muscle involvement like in GSDIIIa. The food composition takes the metabolic defect into account and could have a positive effect on progression.